Improved Confidence Intervals of a Small Probability from Pooled Testing with Misclassification - Liu, Chunling; Liu, Aiyi; Zhang, Bo; Zhang, Zhiwei (Frontiers in Public Health, 2013)
This article concerns construction of confidence intervals of the prevalence of a rare disease using Dorfman's pooled testing procedure when the disease status is classified with an imperfect biomarker. Such an interval can be derived by converting a confidence interval of the probability that a group is tested positive. The Wald confidence intervals based on normal approximation are shown to be inefficient in terms of coverage probability, even for relatively large number of pools. A few alternatives are proposed and their performance is investigated in terms of coverage probability and length of intervals.